Aproximación de sucesiones definidas por recurrencia - Durán, Ana Lía (2011)
It is established that recurrent sequences, xn+1 = f(xn),which converge to a fixed point L where the derivative α = f '(L) satisfies 0 < |α| < 1 and where the rest r(x) = f(x) - L - α(x-L) satisfies r(x) = O(|x - L|1+ s), for some s > 0, can be approximated as xn ~ L + cαn for a certain constant c. It is shown that such approximation might fail if only the condition 0 < |α| < 1 is assumed.